Keterkaitan kebiasaan manusia terhadap kondisi gigi - Widya Ayu Permatasari; Myrtati D Artaria (Faculty of Social and Political Science, Universitas Airlangga, 2015)
Many daily habits relates to the condition of dentition. Therefore it is interesting to study in the coastal society that has unique daily habit and food, that may affect the condition of their dentition. This research used ethnography method. This method has two way to get information, (1) interview and (2) observation. Researcher lived in Dusun Tawang Kulon, District Sidomulyo, sub Ngadirojo, Pacitan for 1 month. Researcher interviewed 19 people age 30-90 years old and experienced tooth illnesses condition. Qualitative data analysis use data collection, categorization of the data obtained, resulting domain, interpretation and conclusions. The result of this research shows that society in Tawang Kulon, District Sidomulyo, sub Ngadirojo practice several types of behavior that relate to tooth condition. That three types human behavior are (1) dietary behavior, for example is how to make gaplek flour and food flavour, (2) incidental cultural behavior, for example using tooth-picks (3) intentional cultural modification, for example nginang—bethel nut chewing, and pangur—teeth-filing. In term of oral health, prevention is not very common. As long as the society did not feel any pain, they did not seek for medication. When there is tooth-ache, first, they did nothing expecting the pain will go away by itself. Second they will try heal using traditional medication or over-the-counter medication such as pain killer. If the pain persists, then, they visit the dentist or dental nurse.